Rango de extensión de la rata acuática peruana Neusticomys peruviensis (Rodentia: Cricetidae) en Perú - Gonzales, Fiorella N. (2017)
Neusticomys peruviensis (Musser & Gardner 1974) is a semi aquatic rodent which belongs to the Ichthyomyini Tribe. It is an endemic species of Peru, previously known for three specimens: type specimen from Balta, another specimen from Rio Shesha, both from Ucayali department; and the third specimen from Pakitza (Madre de Dios department). We captured an additional specimen in Cusco Department. Its geographic distribution extends 84.15 km south of the previously known distribution range.  This suggest that this species would have a broader distribution. More detailed studies are needed to know the ecology and distribution of these rodents.